Service quality transformation and its impact on customer satisfaction and loyalty in Malaysian retail banking sector - Annamalah, Sanmugam; Munusamy, Jayaraman; Chelliah, Shankar; Sulaiman, Mohamed; Pandian, Sivamurugan (IDOSI Publication, 2011)

(untitled)
This paper investigates the importance of antecedents of customer loyalty such as customer satisfaction and service quality dimensions. It addresses whether the dimensions of service quality impacts customer satisfaction eventually leading to customer loyalty. The Structural Equation modeling technique was used in this analysis to determine customer satisfaction and customer loyalty. The results suggest that empathy and assurance are the key factors in delivering customer satisfaction, whereas, tangibility, reliability and responsiveness are found to least impacting customer satisfaction. The relationship between customer satisfaction and customer loyalty is also found to be very significant. Therefore, the bank managers should focus their resources on improving customer care and assuring the services provided to the bank customers will eventually create customer loyalty towards their banks.